Development Of Small Medium Entreprise With External, Internal, And Religiosity Factors In Islamic Banks - Aziz, Roikhan Mochamad (KINERJA, 2017)
The purpose of this research is to analyze the influence of external, internal and religiosity variable that proxies to inflation, Bank Indonesia Certificate Sharia (SBIS), Non Performing Financing (NPF) and Third Party Fund (DPK) to Small and Medium Enterprises Financing in the Islamic Bank in Indonesia. The data is used Time Series data periods of January: 2011 – March: 2016 from Statistic Banking of Indonesia by analyzed of Multiple Linear Regression and Hahslm method. The results of this research indicate that the variable Inflation, Bank Indonesia Sharia Certificate (SBIS), Non Performing Financing (NPF) and Third Party Fund (DPK) have partially influence to Small and Medium Enterprises Financing. This is showed by the value of Adjusted R Square of 60,7% while the remaining 39,3% influence by other factors. In this research showed Inflation, Non Performing Financing (NPF) and Third Party Fund (DPK) have a significantly and positive effect on the Small and Medium Enterprises Financing. Meanwhile, Bank Indonesia Sharia Certificate (SBIS) has no significantly effect on Small and Medium Enterprises Financing. Simultaneously, the overall independent variables have a significant influence to Small and Medium Enterprises Financing.Keywords: Inflation, SBIS, NPF, Islamic Banking.